Designcommunication – a facilitator of creativity for all - Galla, Daniella Dominika; Horváth, Dóra; Cosovan, Attila Róbert (Creativity Studies, 2024)
Our goal is to introduce the term designcommunication written in one word, a creative, academically based design approach combining theory and practical experience as good as possible in various application settings, be it education, scientific research, concept, product or system development. Designcommunication provides a highly flexible framework and a sound methodological base beyond the familiar. Designcommunication, in other words, creating a connection as designing, is an approach that uses a holistic triple relation framework of opposing dimensions: material–immaterial, permanent–variable and survival–subsistence–development relations. This framework of relations is available and possibly applicable to anyone regardless of level and area of education. Introducing such a design approach to education opens new horizons of creative cooperation, as designcommunication facilitates the development of creativity, collaboration and communication as increasingly valued soft skills.